Rozwiąż równanie:
a) -4(2x-5)=2(3x+7)
B)⅔x-13=⅓(x+9)
C)⅗(2x-7)=7/15(3+x)
D)5x-4/6-7-2x/2=0
E)x(x-3)=(x+2)²
F)x(3-x)/3-3-2x²/6=2x

znak "/" zastepuje ułamek

-x²-x-1 dla x=½

doprowadź do najprostszej postaci:
a) (a-3)(2a-5)-(3a+1)²
B) (3a-b)²+(a-2b)(a+2b)-3a(2a-b)

za wszystkie rozwiązania daje naj :)

3

Odpowiedzi

2010-03-04T15:25:26+01:00
A) -4(2x-5)=2(3x+7)
-8x+20=6x+14
-8x-6x=14-20
-14x=-6 |:(-14)
x=³/₇

b) ⅔x-13=⅓(x+9)
⅔x-13=⅓x+3
⅔x-⅓x=3+13
⅓x=16 |:⅓
x=48

c) ⅗(2x-7)=7/15(3+x)
1⅕x-4⅕=7/45+15x |*45+15x
(1⅕x-4⅕)*(45+15x)=7
54x+18x²-189-63x=7
9x+18x²=7+189
9x+18x²=196 |:9
x+2x²=21 |:2
½x+x²=10,5 (?)

d)5x-4/6-7-2x/2=0
5x-4-2x/2=0 |*2
10x-8-2x=0
8x=8
x=1

e) x(x-3)=(x+2)²
x²-3x=x²+4x-4
-7x=-4 |:(-7)
x=⁴/₇

f) x(3-x)/3-3-2x²/6=2x
3x-x²/3-3-2x²/6=2x |*6
6x-2x²-3-2x²=2x
4x-4x²=3 |:4
x-x²=¾


-x²-x-1 dla x=½
-(½)²-½-1=-1¼

a) (a-3)(2a-5)-(3a+1)²=2a²-5a-6a+15-(9a²+6a+1)= 2a²-5a-6a+15-9a²-6a-1=-7a²-17a+14
B) (3a-b)²+(a-2b)(a+2b)-3a(2a-b) =9a²-6ab+b²+a²-4b²-6a²+3ab=4a²-3ab-3b²

sprawdź jeszcze.
Najlepsza Odpowiedź!
2010-03-04T15:29:28+01:00
A) -4(2x-5)=2(3x+7)
-8x+20=6x+14
-8x-6x=14-20
-14x=-6 /:-14
x=3/7

⅔x-13=⅓(x+9)
⅔x-13=⅓x+3
⅔x-⅓x=3+13
⅓x=16 /*3
x=48

⅗(2x-7)=7/15(3+x)
6/5x-21/5=21/15+7/15x
18/15x-63/15=21/15+7/15x /*15
18x-63=21+7x
18x-7x=21+63
11x=84 /:11
x=84/11


5x-4/6-7-2x/2=0
5x-4/6 -3(7-2x)/6=0 /*6
5x-4-21+6x=0
11x=21+4
11x=25 /:11
x=25/11

x(x-3)=(x+2)²
x²-3x=x²+2x+4
-3x-2x=4
-5x=4 /:(-5)
x=-4/5

x(3-x)/3-3-2x²/6=2x
2x(3-x)/6 - 3-2x²/6=2x /*6
6x-2x²-3+2x²=12x
6x-12x=3
-6x=3 /:(-6)
x=-½


-x²-x-1 x=½
(-½)²+½-1=¼+½+1=7/4

(a-3)(2a-5)-(3a+1)²=2a²-5a-6a+15-(9a²+3a+1)=2a²-11a+15-9a²-3a-1=
-7a²-14a+14

(3a-b)²+(a-2b)(a+2b)-3a(2a-b)=9a²-3ab+b²+a²-4b²-6a²+3ab=
4a²-3b²


2010-03-04T17:19:00+01:00
A) -4(2x-5)=2(3x+7)
-8x+20=6x+14
-8x-6x=14-20
-14x=-6 |:(-14)
x=³/₇

b) ⅔x-13=⅓(x+9)
⅔x-13=⅓x+3
⅔x-⅓x=3+13
⅓x=16 |:⅓
x=48

c) ⅗(2x-7)=7/15(3+x)
1⅕x-4⅕=7/45+15x |*45+15x
(1⅕x-4⅕)*(45+15x)=7
54x+18x²-189-63x=7
9x+18x²=7+189
9x+18x²=196 |:9
x+2x²=21 |:2
½x+x²=10,5 (?)

d)5x-4/6-7-2x/2=0
5x-4-2x/2=0 |*2
10x-8-2x=0
8x=8
x=1

e) x(x-3)=(x+2)²
x²-3x=x²+4x-4
-7x=-4 |:(-7)
x=⁴/₇

f) x(3-x)/3-3-2x²/6=2x
3x-x²/3-3-2x²/6=2x |*6
6x-2x²-3-2x²=2x
4x-4x²=3 |:4
x-x²=¾


-x²-x-1 dla x=½
-(½)²-½-1=-1¼

a) (a-3)(2a-5)-(3a+1)²=2a²-5a-6a+15-(9a²+6a+1)= 2a²-5a-6a+15-9a²-6a-1=-7a²-17a+14
B) (3a-b)²+(a-2b)(a+2b)-3a(2a-b) =9a²-6ab+b²+a²-4b²-6a²+3ab=4a²-3ab-3b²